2013
DOI: 10.1021/jp400910h
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Properties and Spectral Investigation of Dilute SO2in a Triethylene Glycol + Water + La3+ System

Abstract: Isothermal gas-liquid equilibrium (GLE) data were determined for dilute SO2 in a triethylene glycol (TEG) + water (W) system (TEGW) at 298.15 K and 123.15 kPa, in which SO2 partial pressures were calculated in the range 0-130 Pa. When La(3+) was added into TEGWs, GLE data suggested that adding of La(3+) ion markedly increased the solubility of dilute SO2. By fitting of these data, Henry's law constants (HLC) were obtained. For acquiring the important absorption mechanism, UV, FTIR, (1)H NMR, and fluorescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In previous work, solubilities of SO 2 in ethylene glycol and poly(ethylene glycol) have been determined, and the absorption mechanism was discussed. [25][26][27][28] However, as far as we know, few comparisons of the absorption capacity and interaction mechanism have been made among ethylene glycol derivatives. Besides that, an efficient way to explore the interactions between SO 2 and the solvents in the physical absorption process is still in demand.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, solubilities of SO 2 in ethylene glycol and poly(ethylene glycol) have been determined, and the absorption mechanism was discussed. [25][26][27][28] However, as far as we know, few comparisons of the absorption capacity and interaction mechanism have been made among ethylene glycol derivatives. Besides that, an efficient way to explore the interactions between SO 2 and the solvents in the physical absorption process is still in demand.…”
Section: Introductionmentioning
confidence: 99%
“…Figure showed that the solubility of SO 2 in the binary system of TEG (1) + DMSO (2) increased with the increasing DMSO concentrations in the whole mass fraction range. When SO 2 concentration in the gas phase was designed at y SO 2 = 500 × 10 –6 , the solubility of SO 2 in the mixtures presented an extreme minimum value (0.005 mol/kg) at the mass fraction of w 1 = 1.00 (pure TEG); meanwhile, the pure DMSO showed the strongest capability of 0.0781 mol/kg to dissolve SO 2 . These GLE data could give us important information to optimize the composition of the mixture solution during the absorption processes.…”
Section: Resultsmentioning
confidence: 99%
“…GLE data of dilute SO 2 in various TEG (1) + DMSO (2) mixtures were measured at T = (298.15, 303.15, and 308.15) K and p = 123.15 kPa. The experimental instrument and process were identical to the previous works, and the experimental apparatus used in this work was shown in Figure . Before the test was conducted, 400 mL of solvent was poured into the jacketed vessel as the absorption solution; a CS 501 thermostatic bath with a Beckmann thermometer was kept at a constant temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luckily, it was found that alcohol could reduce DMSO's freezing point and improve its SO 2 absorption performance. In these organic binary alcohol + DMSO SO 2 absorption systems [7], TEG, instead of other alcohols, was often used because of its high thermal stability, hypotoxicity and low melting point [8,9]. Up to the present, physical properties, especially density (ρ) and viscosity (η), of the binary system TEG + DMSO have not been studied systematically although they are extremely important in the absorption and desorption processes of SO 2 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%